ANALYSIS OF THE CONSTRUCTION MANAGEMENT OF THE DEVELOPMENT PROJECT BOARDING HOUSE IN TEGAL PARANG, SOUTH JAKARTA - Maulana, Cepi; Anwar, Saihul (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2018)
Project management is all planning, implementation, controlling and coordination a project from early the (idea) the end project to en sure of the project appropriately time, money and quality. Selection method scheduling project is also one the very policy note in order to obtain result in according with the original plans.This thesis specifically discuss how project management planning the construction of a Boarding house Tegal parang, South Jakarta. The research was conducted by means of a survey into the field and study of literature.This thesis analysis includes volume calculation, Needs of labor, materials and equipment, Bar chart, Cash flow, S Curve, method of CPM (Critical Path Method) is a method of identifying critical work paths or items. Forwards calculation, backwards calculation, free float and total float.Keyword: Project Management, Bar Chart, S Curve, Critical Path Method.